Intersex/variations of sex characteristics and DSD citizenship in the UK, Italy and Switzerland. Issue 8 (17th November 2019) - Monro, Surya; Crocetti, Daniela; Yeadon-Lee, Tray
ABSTRACT: Citizenship studies is highly relevant to understanding intersex, variations of sex characteristics (VSC), and Disorders of Sex Development (DSD), yet little scholarship exists to date about intersex citizenship. This article outlines and develops the foundations for a distinctive intersex citizenship studies, addressing health citizenship, children's citizenship, legal rights, and breaches of human rights experienced by intersex people and those with DSD. The paper presents original qualitative data from research in the UK, Italy and Switzerland with intersex people and their advocates, medics, and policy stakeholders. It shows that asserting citizenship is crucial for intersex people and those with VSC or DSD. This extremely marginalised population require social, intimate, children's and health citizenship. Intersex citizenship addresses both medical and human rights issues in an integrated way.